2018
DOI: 10.3390/molecules23061434
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of FT-IR Fingerprint and α-Glucosidase Inhibitory Activity of Salak (Salacca zalacca) Fruit Extracts Utilizing Orthogonal Partial Least Square

Abstract: Salak fruit (Salacca zalacca), commonly known as snake fruit, is used indigenously as food and for medicinal applications in Southeast Asia. This study was conducted to evaluate the α-glucosidase inhibitory activity of salak fruit extracts in correlation to its Fourier transform infrared spectroscopy (FT-IR) fingerprint, utilizing orthogonal partial least square. This calibration model was applied to develop a rapid analytical method tool for quality control of this fruit. A total of 36 extracts prepared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…On the other hand, the α-glucosidase inhibitory activity followed a different trend, with the lowest potential attributed to the water extract (IC 50 = 95.32 ± 2.32 µg/mL) followed by the 20% methanol extract (IC 50 = 56.56 ± 1.68 µg/mL), while the highest activity (IC 50 = 19.54 ± 2.5 µg/mL to 23.46 ± 3.91 µg/mL) was exhibited by the 40%, 60%, 80% and 100% methanol extracts, which were not significantly different from each other at p < 0.05. These results are consistent with [11,23,28] who have reported that the higher α-glucosidase inhibitory activity was associated with the higher alcohol to water ratios of the extractant mixtures, and vice versa.…”
Section: Extraction Yield and α-Glucosidase Inhibitory Activitysupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, the α-glucosidase inhibitory activity followed a different trend, with the lowest potential attributed to the water extract (IC 50 = 95.32 ± 2.32 µg/mL) followed by the 20% methanol extract (IC 50 = 56.56 ± 1.68 µg/mL), while the highest activity (IC 50 = 19.54 ± 2.5 µg/mL to 23.46 ± 3.91 µg/mL) was exhibited by the 40%, 60%, 80% and 100% methanol extracts, which were not significantly different from each other at p < 0.05. These results are consistent with [11,23,28] who have reported that the higher α-glucosidase inhibitory activity was associated with the higher alcohol to water ratios of the extractant mixtures, and vice versa.…”
Section: Extraction Yield and α-Glucosidase Inhibitory Activitysupporting
confidence: 92%
“…The method reported by Saleh et al [23] was followed for assessment of the α-glucosidase inhibitory potential of T. scandens extracts, with slight modifications. Quercetin (positive control) and the lyophilized plant extracts were dissolved in DMSO to obtain stock solutions of concentrations 2 and 4 mg/mL, respectively.…”
Section: Assay Of α-Glucosidase Inhibitory Activitymentioning
confidence: 99%
“…In this study, different ratios of aqueous methanolic solvent were investigated, which led to obtaining an extract with high AGI activity in 100% methanol. The trend of AGI activity (100 > 25 > 50 > 0 > 75% v/v methanol-water) is caused by the difference of metabolite profiling among the extracts which were affected by the solvent used during extraction [42][43][44][45]. Table 3 shows the binding interactions of compounds 1, 2, and 3.…”
Section: Discussionmentioning
confidence: 99%
“…Pericarps from P. speciosa show significant inhibitory activity (IC 50 0.0581 mg/mL; 89.46%) against α-glucosidase [ 156 ], an enzyme responsible for breaking down starch and polysaccharide into glucose [ 159 ]. The seeds also show inhibitory activity but at lower percentage (45.72%) [ 156 ].…”
Section: Pharmacological Activities Of Parkia Smentioning
confidence: 99%